PENGARUH PENGERINGAN TERHADAP LAJU PENURUNAN KADAR AIR DAN BERAT JAGUNG (Zea mays L.) UNTUK VARIETAS BISI 2 dan NK22 - Muh Arsyad (Agropolitan, 2018)
The aimed of this research is to know the influence of drying to moisture content and weight for hybrid maize Bisi 2 and NK22 and to determined the optimal drying time on those both varieties. The experiment was carried out by drying for four days of drying using Randomized Complete Random Design (RAL) two factorials that is drying day factor with varieties and if significantly different then followed by BNJ advanced test. The results of this study showed that drying on corn both varieties of Bisi 2 and NK22 to moisture content and weight of maize decreased, for NK22 varieties more weight decrease compared with Bisi 2. Effect of drying time and varieties used very significant effect on water content and corn weight. The optimum drying time for the bisi 2 and NK22 was two days drying so that moisture content under 14% or in accordance with Indonesian national standards and the weight of maize was not much decreased.